Changes in glycosylated haemoglobin after oral glucose load. Issue 6296 (3rd October 1981) - Scobie, I N; Onyanga-Omara, F; Singaraveloo, M; Forrest, A R; MacCuish, A C; Manderson, W G
Abstract : To study the relation between hyperglycaemia and a change in the concentration of glycosylated haemoglobin (HbA1) blood glucose and HbA1 concentrations were measured during an oral glucose tolerance test and for 120 days afterwards in 20 normal subjects. These measurements showed that a minor degree of hyperglycaemia led to a significant increase in lycosylated haemoglobin concentrations. The increase appeared 10 days after the test, and values remained raised until 30 days and returned to normal 60 days after the test. If such a minor fluctuation of blood glucose can lead to a significant increase in HbA1 concentrations the test may be too sensitive as an index of long-term blood glucose control in diabetics.